Antidiarrheal Potential of Maja (Crescentia cujete) Fruit Extract in Mice - Teodhora, Teodhora; Manalu, Rosario Trijuliamos; Saputra, Richi Andika (Borneo Journal of Pharmacy, 2024)
Diarrhea, characterized by frequent, loose stools, can be treated with various approaches. This study investigated the antidiarrheal properties of maja (Cresentia cujete) fruit extract, which contains secondary metabolites like tannins and flavonoids with astringent properties. The objective was to determine the optimal dose of C. cujete fruit extract for treating diarrhea in mice. An in vivo experimental design was employed, inducing diarrhea in male mice using oleum ricini. The study assessed stools' onset, duration, consistency, frequency, and weight. Cresentia cujete fruit extract was administered orally at 125, 250, and 500 mg/kg BW doses. A comparison was made with negative control (CMC-NA) and positive controls (loperamide and attapulgite). Data analysis involved ANOVA followed by the Tukey test. The findings revealed that 500 mg/kg BW of C. cujete fruit extract was the most effective dose for treating diarrhea in mice. These results suggest the potential of C. cujete fruit extract as a promising natural antidiarrheal agent.